Aspiring personality: Patients waiting for obesity treatment. Issue 2 (26th March 2018) - Garcia, Danilo; Forssell, Henrik; Cloninger, Kevin M.
Abstract: The aim of the present study was to investigate differences in temperament and character between patients ( N  = 70) waiting for obesity surgery and the general population. Patients waiting for obesity surgery scored higher in Harm‐Avoidance, Reward Dependence, Persistence, and Cooperativeness and also lower in Self‐Directedness.